A content analysis of the portrayal of alcohol in televised music videos in New Zealand: Changes over time. (10th June 2012) - Sloane, Kate; Wilson, Nick; Imlach Gunasekara, Fiona
Abstract Introduction and Aims We aimed to: (i) document the extent and nature of alcohol portrayal in televised music videos in New Zealand in 2010; and (ii) assess trends over time by comparing with a similar 2005 sample. Design and Methods We undertook a content analysis for references to alcohol in 861 music videos shown on a youth‐orientated television channel in New Zealand. This was compared with a sample in 2005 (564 music videos on the same channel plus sampling from two other channels). Results The proportion of alcohol content in the music videos was slightly higher in 2010 than for the same channel in the 2005 sample (19.5% vs. 15.7%) but this difference was not statistically significant. Only in the genre 'Rhythm and Blues' was the increase over time significant (P = 0.015). In both studies, the portrayal of alcohol was significantly more common in music videos where the main artist was international (not from New Zealand). Furthermore, in the music videos with alcohol content, at least a third of the time, alcohol was shown being consumed and the main artist was involved with alcohol. In only 2% (in 2005) and 4% (in 2010) of these videos was the tone explicitly negative towards alcohol. Discussion and Conclusions In both these studies, the portrayal of alcohol was relatively common in music videos. Nevertheless, there are various ways that policy makers can denormalise alcohol in youth‐orientated media such as music videos or to compensate via other alcohol control measures such as higher alcohol taxes.